Pelatihan Strategi Peningkatan Pemasaran, Penjualan dan Pelaporan Akuntansi melalui Pembuatan Website di Yayasan Duta Bangsa Indonesia di Cikarang - Cahyadi Husadha; Widi Winarso; Wastam Wahyu Hidayat; Wirawan Widjanarko; Adelina Suryati; Adi Wibowo Noer Fikri (Jurnal Pengabdian kepada Masyarakat UBJ, 2020)
Duta Bangsa College of Technology was established on March 3, 2007 in accordance with the Decree of the Minister of Education and Culture Number.34/D/0/2007 concerning the establishment of STT.Duta Bangsa. STT.Duta Bangsa is located in Kp. Pulokapuk RT 01 RW 05 Mekar Mukti Village Kec. North Cikarang Kab. Bekasi. Tel/Fax number: (021) 29082747. Permit of Higher Education: Minister of Education Decree No.2740/D/T/K-IV/2010. Minister of Education Decree No.2741/D/T/K-IV/2010. Decree of Minister of National Education No.2742/D/T/K-IV/2010. The problem faced by the Indonesian ambasadors foundation is the marketing problem, where they have to compete in fighting over a limited market niche with more and more competitors. Moreover, the market share to fight over the students who are nota bene is the X generation who are literate in the world of Information Technology, which certainly requires marketing to hit their hearts. Starting from this, we from the Faculty of Economics at Bhayangkara University offered to provide training for Marketing Persons at the Duta Bangsa Foundation so that they could win a large market share of students in Bekasi, especially in the Cikarang area, in creating a web site.